Combustion analysis of CuO2 nanoparticle addition with blend of botryococcus braunii algae biodiesel on CI engine. (2020) - Dharmaprabhakaran, T.; Karthikeyan, S.; Periyasamy, M.; Mahendran, G.
Abstract: The energy crisis is attributed to two reasons: one is the rapid growth of the global human population and the other is the evolution of the human lifestyle. Modern oil is also a key component in introducing contaminants to the atmosphere. Changes in fuel consumption play a key role in increasing engine efficiency and reducing emissions. In the current research, fuel changes in the diesel engine were developed. The single-cylinder diesel engine was initially equipped with botryococcus braunii algae oil methyl ester and its diesel blends with CuO2 nano additives B20, B20 + 25 ppm, B20 + 50 ppm, B20 + 75 ppm, B20 + 100 ppm at different loads at steady engine speed. From the experimental analysis, it has been shown that B20 is the more efficient fuel ratio than other blends. The results showed a significant reduction in CO, HC and smoke emissions. The current analysis shows that BBAME's biodiesel with CuO2 nano additives is best suited as an alternative diesel engine fuel.